Enhancement of cell migration and wound healing by nano-herb ointment formulated with biosurfactant, silver nanoparticles and Tridax procumbens - Muthukumar, Balakrishnan; Nandini, M. S.; Elumalai, Punniyakotti; Balakrishnan, Muthuraj; Satheeshkumar, Azhargarsamy; AlSalhi, Mohamad S.; Devanesan, Sandhanasamy; Parthipan, Punniyakotti; Rajasekar, Aruliah; Malik, Tabarak (Frontiers in Microbiology, 2023)
Introduction Ointments are generally used as a therapeutic agent for topical medication or transdermal drug delivery, such as wound healing and skin lesions. Methods In this study, Tridax procumbens plant extract (0.7 g/mL) was used to prepare herbal-infused oil as the oil phase and gelatin-stabilized silver nanoparticle (G-AgNPs) (0.3 g/mL) as the aqueous phase. To blend the oil and aqueous phases, rhamnolipid biosurfactant with a critical micelle concentration of 55 mg/L from strain Pseudomonas aeruginosa PP4 has been used for herb ointment preparation. The average size of the synthesized G-AgNPs was observed between 10–30 nm and confirmed as spherical-shaped particles by TEM analysis. Subsequently, GC–MS and FTIR characterization are used to confirm herb ointment’s chemical and functional characteristics. Results Based on the antibacterial studies, the highest microbial growth inhibition was observed for herb ointment, about 19.5 mm for the pathogen Staphylococcus aureus at the concentration of 100 μg/mL, whereas 15.5 mm was obtained for Escherichia coli, respectively. In addition, the minimum inhibitory concentration (MIC) assay showed negligible bacterial growth at 100 μg/mL for S. aureus and E. coli, respectively. Moreover, the cell viability assay for herb ointment exhibited low cytotoxic activity at higher concentrations (100 μg/mL) in Vero cell lines. In this study, wound scratch assay showed a significant cell migration rate (90 ± 2%) in 3 days of incubation than the control (62 ± 2%). Discussion As a result, the biosurfactant-based nano-topical herb ointment revealed a low cytotoxic and higher cell migration capacity. Altogether, these findings highlighted the utility of this herb ointment in therapeutic applications such as wound healing.